MHD mixed convection of nanofluids in the presence of multiple rotating cylinders in different configurations: A two-phase numerical study. (January 2019) - Daneshvar Garmroodi, M.R.; Ahmadpour, A.; Talati, F.
Highlights: Using two rotating cylinders enhances the mixed convection heat transfer for nanofluids. A vertical arrangement for two cylinders possesses the highest heat transfer rate. Heat transfer rate increases monotonically with solid mass fraction. Increasing Hartman number, reduce rate of heat transfer. Effect of Hartman number is more significant in vertical alignment. Abstract: In the present study, MHD laminar mixed convection of Cu/water nanofluid inside a lid driven cavity and in the presence of two rotating cylinders is numerically simulated. This mixed convection problem has found its applications in material processing, air conditioning, electronic cooling, solar heating/cooling and other natural and industrial processes. A two phase mixture model is adapted for the simulation of nanofluid flow and heat transfer and the well-known finite volume approach was employed to discretized the governing equations. A comprehensive parametric study was carried out in order to delineate the effect of various relevant variables including angular velocities of cylinders, the intensity of natural convection, the nanoparticles volume fraction, the arrangement of two cylinders inside the cavity and the Hartmann number on the fluid flow and heat transfer in the presence/absence of an external magnetic field. It was shown that using two insulated rotating cylinders enhances the mixed convection for nanofluids provided that their direction of rotation, the magnitude of their angular speeds and their relative arrangement are adjusted properly as it is suggested in the present study. To achieve the maximum enhancement for the heat transfer rate, the use of a vertical arrangement for the cylinders is advised. Moreover, heat transfer rate decreases with the Hartmann number and the effect of an external magnetic field is the most significant when two cylinders are aligned vertically. Graphical abstract: The use of two rotating cylinders for nanofluid heat transfer enhancement is addressed within a lid driven cavity in the presence/absence of an external magnetic field. The effect of various relevant variables including angular velocities of cylinders, the intensity of natural convection, the nanoparticles mass fraction and the arrangement of two cylinders inside the cavity on the fluid flow and heat transfer is investigated thoroughly.